2006
DOI: 10.1021/ja060021e
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Surfactant Vesicles that Transform into Viscoelastic Wormlike Micelles upon Heating

Abstract: Unilamellar vesicles are observed to form in aqueous solutions of the cationic surfactant, cetyl trimethylammonium bromide (CTAB), when 5-methyl salicylic acid (5mS) is added at slightly larger than equimolar concentrations. When these vesicles are heated above a critical temperature, they transform into long, flexible wormlike micelles. In this process, the solutions switch from low-viscosity, Newtonian fluids to viscoelastic, shear-thinning fluids having much larger zero-shear viscosities (e.g., 1000-fold hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
297
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(321 citation statements)
references
References 18 publications
17
297
2
1
Order By: Relevance
“…При этом многими авторами отмечено, что для молекул катионного ПАВ цетилтриметиламмоний бромида (ЦТАБ), находящихся в водных растворах, характерно появление наноструктурных образований в виде везикул обычно стандартной сферической формы [14]. В работе [15] нами было показано, что молекулы ЦТАБ могут спонтанно организо-вываться в гораздо более сложные структуры с характерным размером в несколько десятков микрометров.…”
Section: результаты и их обсуждениеunclassified
“…При этом многими авторами отмечено, что для молекул катионного ПАВ цетилтриметиламмоний бромида (ЦТАБ), находящихся в водных растворах, характерно появление наноструктурных образований в виде везикул обычно стандартной сферической формы [14]. В работе [15] нами было показано, что молекулы ЦТАБ могут спонтанно организо-вываться в гораздо более сложные структуры с характерным размером в несколько десятков микрометров.…”
Section: результаты и их обсуждениеunclassified
“…All the flow curves for MX 2,5-Cl 2 Bz Na of the origin of these maxima is not fully understood at the molecular level 13,31,36 . However, it has become almost certain from these studies 13, 30 35 of CTABr micellar-mediated piperidinolysis of PSa have been described elsewhere 38,40 .…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…Kreke et al used 1 H and 13 C NMR studies to show that 2,6-Cl 2 C 6 H 3 CO 2 2,6-Cl 2 Bz and 3,5-Cl 2 Bz counterions were intercalated within the cationic micellar headgroups and that 3,5-Cl 2 Bz counterions inserted further into the interface of rodlike micelles while 2,6-Cl 2 Bz counterions remained at the surface of the spherical micelles 25 . Based upon 1 H, 19 F and 13 C NMR studies, Vermuthen et al concluded that the 2-FC 6 H 4 CO 2 2-FBz counterion penetrates the micellar interface more deeply than 3-FBz and 4-FBz counterions 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Small-angle neutron scattering and dynamic light scattering studies have reported on isotropic to nematic phase transitions, 23 transitions from vesicles to wormlike micelles, 30 the concentration dependence of the hydrodynamic correlation length, 31 and the effect of adding salt on micellar growth. 32 Scattering measurements have also characterized important lengths of the micellar network 33 and have been used to investigate local structure and flexibility.…”
Section: 29mentioning
confidence: 99%